The H19/let-7 feedback loop contributes to developmental dysplasia and dislocation of the hip - Ning, Bo; Jin, Rui; Wang, Dahui; Sun, Jun (Physiological research, 2019)
Developmental dysplasia and dislocation of the hip (DDH) is the most common type of lower limb deformity in pediatric orthopedics. The mechanism of the signaling pathway has been studied in depth. However, the role of epigenetic regulation, such as lncRNA, is still far from clear. In this study, we successfully established a rat model of DDH and demonstrated that H19 was down-regulated in the development of DDH. Further, we constructed H19 knockdown (KD) and overexpression chondrocytes. H19 KD suppressed the proliferation of normal chondrocytes, while overexpression of H19 promoted cell proliferation of DDH chondrocytes. Finally, we revealed that H19 bound to let-7 and inhibited its function, acting as a competing endogenous RNA. Down-regulation of H19 is closely associated with DDH progression and H19 is an important epigenetic factor that regulates the proliferation of chondrocytes. H19 may thus be a potential clinical marker for DDH diagnosis and treatment.
Keywords: zpětná vazba fyziologická; Pregnancy; Epigenesis, Genetic; vývojová kyčelní dysplazie; RNA, Long Noncoding; MicroRNAs; RNA dlouhá nekódující; Female; novorozená zvířata; krysa rodu Rattus; zvířata; proliferace buněk; Cells, Cultured; chondrocyty; potkani Wistar; epigeneze genetická; Animals, Newborn; ženské pohlaví; Rats, Wistar; kultivované buňky; Cell Proliferation; těhotenství; Hip Dislocation, Congenital; Rats; mikro RNA; Animals; Chondrocytes; Feedback, Physiological